PEMANFAATAN MARKETPLACE DAN MEDIA SOSIAL DALAM PENINGKATAN PENJUALAN UMKM DI DESA BINTAN BUYU - Pardede, Ranat Mulia; Sambodo, Bambang; Handayani, Apri; Herfiyansyah, Febri; Nurhildayanti, Fitri; Anza, Friel Methdria; Rahayu, Sri (P3M STIE Pembangunan Tanjungpinang, 2025)
Real Work Lecture (KKN) conducts a work program regarding the marketplace. In implementing the program, it can be seen that one of the problems that occur in Micro, Small and Medium Enterprises (MSME) in Bintan Buyu Village is one of the problems in promoting their products. These MSME are still not actively promoting their products on social media such as Instagram, Facebook, and WhatsApp Business because they only do sales and marketing in their surroundings. The targets of the MSME studied were Sweet Spicy Potato Chips and Peanut Cake. In its implementation, this KKN work program conducts outreach regarding marketplaces and conducts training on creating social media accounts and marketing products on social media. The results of the work program regarding this marketplace are increasing sales of the two targeted MSME. This is because the use of marketplaces and social media is very influential in increasing sales. Because social media can reach consumers widely and not only in the surrounding environment, and can make it easier for MSME to market their products..